Covenant and Salvation in the Old Testament: Examining the role of covenants in the Old Testament as mechanisms for salvation, considering the Abrahamic, Mosaic, and Davidic covenants - Manurung, Freddy (Jurnal Koinonia: Fakultas Filsafat Universitas Advent Indonesia, 2024)
This research examines the role of the Abrahamic, Mosaic, and Davidic covenants in the Old Testament as key mechanisms for salvation. Derived from the Hebrew term berith, a covenant is a divine agreement establishing a relationship between God and His people. Each covenant plays a pivotal role in salvation history, revealing God's character and redemptive plan. The Abrahamic Covenant promises land, descendants, and blessings, forming the foundation of Israel's identity. The Mosaic Covenant, given at Mount Sinai, provides the Law as a guide for righteous living. The Davidic Covenant guarantees an eternal kingdom through David’s lineage, pointing to the messianic hope. Despite their importance, there is limited research on the covenants as interconnected aspects of salvation. This study addresses key questions regarding their theological implications and relevance for modern discussions on salvation. Using qualitative methods, the research analyzes key Old Testament passages and secondary sources to explore their historical context, themes, and salvation implications. The findings reveal that these covenants illustrate God's relational approach to humanity, emphasizing grace, faith, and obedience. Understanding these covenants is essential for grasping salvation in both the Old and New Testaments. This study highlights the interconnectedness of the covenants, deepening our understanding of God's redemptive plan and its impact on contemporary theology.